Pengaruh Daya Tarik Wisata dan Aksesibilitas Terhadap Minat Berkunjung di Kampung Cakrawala Kabupaten Sukabumi - Safari, Apay; Edison, Emron; Gita, Vania (Manajemen dan Pariwisata, 2025)
The research was conducted in Kampung Cakrawala, Sukabumi Regency, under the title "The Influence of Tourist Attractions and Accessibility on the Interest in Visiting Kampung Cakrawala, Sukabumi Regency." The purpose of this study was to determine the extent to which tourist attractions and accessibility influence tourists' interest in visiting the destination. This research employed a quantitative approach using descriptive and verification analysis methods, with data collected through questionnaires distributed to 100 respondents who had visited Kampung Cakrawala. The variables examined in this study included tourist attractions, accessibility, and interest in visiting. The results of the descriptive analysis indicated that all three variables were rated in the good category. Furthermore, the results of the verification analysis showed that tourist attractions and accessibility simultaneously had a positive and significant influence on the interest in visiting, with a contribution of 58%, while the remaining 42% was influenced by other factors beyond the scope of this study. These findings suggest that efforts to enhance tourist attractions and improve accessibility can serve as effective strategies to increase tourist interest and the number of visits to Kampung Cakrawala.